Isolated Single Umbilical Artery and Histomorphometric Changes of Umbilical Blood Vessels in Intrauterine Growth Retarded Foetus in Comparison to Normal Neonates - Dinesh Kumar; Jagdish S. Soni (Journal of Pharmacy and Bioallied Sciences)
Background: Three vessels—one vein and two arteries—allow the fetus and placenta to exchange waste, oxygen, and nutrients in the umbilical cord. Single umbilical artery (SUA), a congenital abnormality with one umbilical artery, can occur in some pregnancies. Materials and Methods: The current observational study was conducted at the Parul Institute of Medical Sciences and Research, Waghodia, Vadodara, Gujarat. Ten percent formalin was used to preserve 5 cm segment of the placental cord after delivery. Paraffin-embedded slices were produced, and H and E staining was performed on a 3 μm segment. Results: This study compared 125 normal and 125 intrauterine growth restriction (IUGR) infant umbilical cords. IUGR neonates had significantly thinner umbilical vessel walls than normal newborns, although their cross-sectional area was similar between sexes. Conclusion: The thickness of umbilical cord blood arteries affects IUGR, according to this study. These large vessel wall thickness changes may indicate IUGR or associated disorders.